1998
DOI: 10.1021/es9803106
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Naphthalenes and Coplanar Polychlorinated Biphenyls in Arctic Air

Abstract: Concentrations of polychlorinated naphthalenes (PCNs) are reported for the first time in arctic air. The data represent combined air samples from the Barents Sea (n = 2), eastern Arctic Ocean (n = 10), Norwegian Sea (n = 2), and two land-based monitoring stations at Alert, Canada (n = 5), and Dunai Island in eastern Siberia, Russia (n = 3). Values for ∑PCN (pg m-3) were 6−49 for shipboard samples and 0.3−8 for land-based stations and were dominated by the 3-Cl and 4-Cl homologues, which accounted for 90−95% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
74
3
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 27 publications
(48 reference statements)
12
74
3
1
Order By: Relevance
“…Being consistent to the spatial pattern of PCN concentrations, TEQ values of samples 11 and 13 were higher than others. Compared with other studies, TEQs were slightly higher than those in the arctic air monitoring stations (0.0001-0.0455 fg m − 3 ) (Helm et al, 2004), and considerably lower than those reported for the Barents Sea (0.99 fg m −3 ), the Norwegian Sea (0.36 fg m −3 ), and the eastern Arctic Ocean (0.548 fg m −3 ) (Harner et al, 1998). Much higher TEQ values have been estimated for the air in adjacent countries such as Pakistan and India (Mahmood et al, 2014;Xu et al, 2014).…”
Section: Potential Toxicitycontrasting
confidence: 83%
See 1 more Smart Citation
“…Being consistent to the spatial pattern of PCN concentrations, TEQ values of samples 11 and 13 were higher than others. Compared with other studies, TEQs were slightly higher than those in the arctic air monitoring stations (0.0001-0.0455 fg m − 3 ) (Helm et al, 2004), and considerably lower than those reported for the Barents Sea (0.99 fg m −3 ), the Norwegian Sea (0.36 fg m −3 ), and the eastern Arctic Ocean (0.548 fg m −3 ) (Harner et al, 1998). Much higher TEQ values have been estimated for the air in adjacent countries such as Pakistan and India (Mahmood et al, 2014;Xu et al, 2014).…”
Section: Potential Toxicitycontrasting
confidence: 83%
“…Thus, it is important to monitor marine POP pollution status and estimate their sources. Several studies have been carried out to investigate PCN levels in air, sediments, or organisms of the arctic and subarctic oceans and seas (Falandysz and Rappe, 1996;Harner et al, 1998;Lundgren et al, 2002Lundgren et al, , 2003Bidleman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although the production of PCBs and PCNs has been banned or severely restricted since the 1970s and 1980s, products containing these formulations are still present in the environment (Bidleman et al, 2010;Breivik et al, 2007). In the past two decades, there have been several investigations on the levels, distribution and fate of gaseous PCBs and PCNs in the atmosphere (Falandysz, 1998;Harner et al, 1998;Jaward et al, 2004a;Lee et al, 2007;Mari et al, 2008). The recent researches indicate that historical usage, e-waste and shipwreck are major sources of PCBs (Breivik et al, 2002b;Breivik et al, 2011;Gioia et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the lighter congeners show greater potential to disrupt the thyroid system, which is different from their dioxin-like activities. Of note, most of the PCNs present in air are the lighter congeners; trichlorinated and tetrachlorinated naphthalenes account for approximately 80% and 90-95% of the total PCN mass in ambient and arctic air, respectively, based on air sampling of PCNs in the United Kingdom, and it was concluded that air masses from the United Kingdom and Europe may be influencing PCN burdens more than PCBs [28,29]. Thus, the thyroid-disrupting effects of the lighter congeners may cause severe adverse effects in human acting via airborne exposure.…”
Section: Discussionmentioning
confidence: 99%